Analisa Perilaku Aliran Panas Pada Permukaan Desain Heatsink Dengan Menggunakan Software ANSYS - Aldori, Yopan Rahmad; Pangestu, Reno (CV. IRA PUBLISHING, 2022)
The heatsink is a passive heat transfer device used in an electronic component that has a role as a cooler in the system by utilizing heat distribution and being discharged through the fin gaps on the heatsink, in this article we will discuss analyzing the flow behavior of a heatsink using software ANSYS with a variation of design, the simulation carried out is conditional on placing a heatsink on the surface of a system with a heating temperature of 75oC, with a room temperature of 25oC. In this simulation, various designs will be carried out on the heatsink fins, and the design with the largest heat distribution in this article is design (c) with the simulation results of a flux therma gradient of 7152 W/m2.